The influence of different production systems, planting densities and levels of shading on the yield, quality and growth potential of ‘Chandler’ strawberry plants (Fragaria ananassa) grown in coir - De Villiers, Johannes Jacobus (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScAgric (Agronomy))--Stellenbosch University, 2008.